Characterization Of 2-Dimensional Electrical Resistivity Tomography, Geotechnical And Hydraulic Conductivity Analysis In The Granitic Residual Soil - Olabode, Oladunjoye Peter (2021)
This research aims to characterise 2-D Electrical Resistivity Tomography (ERT) models for changes in soil saturation, analyse geotechnical properties of residual soil for validation of ERT models and develop a relationship between soil resistivity and Hydraulic Conductivity (HC) for lithological characterisation for slope instability assessment.